2018
DOI: 10.1186/s13071-018-3043-x
|View full text |Cite
|
Sign up to set email alerts
|

Duration of annual canine flea and tick protection provided by dog owners in Spain

Abstract: BackgroundDoses of flea and tick medication acquired by dog owners over a 12 month period were determined from veterinary hospital transaction records in Spain. The number of months of flea and tick protection potentially obtained by dog owners prescribed fluralaner, a flea and tick medication with a 12 week re-dosing interval, was compared with months of flea and tick protection obtained by dog owners prescribed monthly oral or spot-on products. Prior studies in human and veterinary medicine have suggested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 16 publications
(14 reference statements)
4
26
0
Order By: Relevance
“…Dog owners that use the 12-week duration fluralaner obtained a 24% increase in months of protection compared with dog owners that obtained monthly afoxolaner and a 73% increase compared with dog owners that obtained monthly spinosad. This finding confirms the results of an earlier study of fluralaner use based on a smaller population of dogs in the USA [ 4 ] and a recent comparative study in Spain [ 15 ].…”
Section: Discussionsupporting
confidence: 91%
“…Dog owners that use the 12-week duration fluralaner obtained a 24% increase in months of protection compared with dog owners that obtained monthly afoxolaner and a 73% increase compared with dog owners that obtained monthly spinosad. This finding confirms the results of an earlier study of fluralaner use based on a smaller population of dogs in the USA [ 4 ] and a recent comparative study in Spain [ 15 ].…”
Section: Discussionsupporting
confidence: 91%
“…Dog owners purchased fewer doses and obtained longer flea and tick treatment coverage per year from fluralaner compared with monthly medications. Similar results were reported in a large-scale European study comparing owner-purchased canine flea and tick medications, comparing oral fluralaner and several monthly oral or topical products [ 31 ]. Dog owners in Spain purchased fewer fluralaner doses per year compared to monthly oral or topical medications but obtained significantly more flea and tick coverage.…”
Section: Discussionsupporting
confidence: 84%
“…Prior studies comparing dog owner flea and tick medication purchases have shown that owners obtain more months of coverage when they buy an extended duration product [ 26 , 31 ]. This study confirms that cat owners similarly will obtain more annual months of flea and tick coverage compared to owners that obtain products with a monthly retreatment interval.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies comparing dog owner ea and tick medication purchases have shown that owners obtain more months of coverage when they buy an extended duration product. 25,30 This study con rms that cat owners show a similar behavior and that when they purchase a ea and tick medication with a 12-week retreatment interval they will obtain more months of ea and tick coverage compared to owners that obtain products with a monthly retreatment interval. Cat owners purchased up to 50% longer duration of ea and tick protection per year when they purchased uralaner, compared with owners who purchased monthly ea and tick medications.…”
Section: Discussionmentioning
confidence: 62%
“…Similar results were reported in a large-scale European study comparing owner-purchased canine ea and tick medications, comparing oral uralaner and several monthly oral or topical products. 30 Dog owners in Spain purchased fewer uralaner doses per year compared to monthly oral or topical medications but obtained signi cantly (P < 0.0001) more ea and tick coverage. Collectively, these studies con rm that pet owners obtain a relatively longer duration of ea and tick control by use of longer duration ea and tick treatments.…”
Section: Discussionmentioning
confidence: 92%